Hubungan Kebiasaan Membaca dengan Hasil Belajar Bahasa Indonesia Siswa Kelas IV SDN 17 Kota Bengkulu - Aptensi, Fenny; Yuliantini, Nani; Lukman, Lukman (Jurnal PGSD, 2018)
This study aims to determine the relationship of the reading habits of learning outcomes Indonesian with fourth grade students of SDN 17 Bengkulu City. This type of research is quantitative with correlational research method. The sample in this study is the fourth grade students of SDN 17  Bengkulu City taken using technique total sampling. The research instrument used was a questionnaire sheet (questionnaire) and interview guidelines and documentation. The technique of collecting data using questionnaires, interviews and documentation. Data analysis techniques in this study using the correlation calculation. product moment. These results indicate that rcount is greater than rtable (0.320 > 0.281). From the statistical calculation result obtained significant valuet is greater than ttable (2,311 ? 1.684) with significance level ? = 0.05 (significance level of 5%), and the contribution of the variable x to y of r = 0.1024, which means that reading habits contributed 10.24% to the Indonesian student learning outcomes. So it can be concluded that there is a significant relationship between the reading habits of learning outcomes Indonesian with fourth grade students of SDN 17 Bengkulu City correlation levels are included in the low category. Thus Ha received and H0 is rejected.